OPTIMASI pH DAN WAKTU KONTAK OPTIMUM ADSORBEN Fe3O4-AH TERHADAP ION LOGAM Pb2+ - Sindi Dwi Riyana; Soerja Koesnarpadi; Ika Yekti Liana Sari (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2022)
Optimization of pH and optimum contact time of coated magnetite adsorbent (Fe3O4-AH) against metal ions Pb2+ has been carried out. Humic acid-coated magnetite adsorbent (Fe3O4-AH) was prepared using the coprecipitation method with a mass ratio of 1:2 (w/w) and the separation process using an external magnet. Optimization was carried out by batch method using a Pb solution with a concentration of 50 mg/L and an adsorbent mass of 0.1 gram Fe3O4-AH. The test results show that the optimum pH is at pH 5 with % adsorption of 97.70% and the optimum contact time is at 20 minutes with % adsorption of 99.89%. Keywords: humic acid, magnetite, adsorption